PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN “TOKO SURVEY” TERHADAP KEMAMPUAN NUMERASI SISWA KELAS III SDIT BAITURRAHMAN CITRA - Resti Larasati; Mohamad Syarif Sumantri, Engga Dallion (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Numeracy skills are the ability to solve everyday problems using various symbols and numbers related to basic mathematics. The purpose of this study is to determine the effect of using the Toko Survey learning media on the numeracy skills of elementary school students. This research employs a quantitative experimental method using a One-Group Pretest and Posttest design. The sample of this study consists of third-grade students at SDIT Baiturrahman Citra. The research shows positive results, as there is a significant increase with an average pretest score of 94.24 and a posttest score of 98.24. The Wilcoxon Signed Rank-Test also indicates a significance value of 0.003 < 0.005, which means there is a significant effect between the pretest and posttest scores. Thus, it can be concluded that the use of Toko Survey media has a real impact on students' numeracy skills in the material of sorting and comparing data.